2019
DOI: 10.1093/jn/nxy303
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks Induce Acute Cardiovascular and Metabolic Changes Pointing to Potential Risks for Young Adults: A Randomized Controlled Trial

Abstract: BackgroundCase reports suggest a link between energy drinks (EDs) and adverse events, including deaths.ObjectivesWe examined cardiovascular and metabolic effects of EDs and mixtures providing relevant ingredients of EDs compared to a similarly composed control product (CP) without these components.MethodsThis randomized, crossover trial comprised 38 adults (19 women, mean BMI 23 kg/m2, mean age 22 y). We examined effects of a single administration of a commercial ED, the CP, and the CP supplemented with major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…The increased heart rate after Red Bull ingestion is in line with previous work performed in man [2][3][4][5]7,11,13,22]. We observed a larger increase of heart rate as we chose a threefold higher amount of Red Bull compared to studies conducted in adults.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increased heart rate after Red Bull ingestion is in line with previous work performed in man [2][3][4][5]7,11,13,22]. We observed a larger increase of heart rate as we chose a threefold higher amount of Red Bull compared to studies conducted in adults.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, such an increased heart rate has been shown during a mental arithmetic task in 20 young healthy adults [7]. A current randomized, crossover trial subjecting 38 healthy adults to several caffeinated energy drinks showed an increased mean arterial blood pressure (MAP), QTc interval and heart rate [13]. These findings are supported by other studies [4,5,11].…”
Section: Introductionsupporting
confidence: 71%
“…A study by Magkos et al [14] emphasized that the physiological changes triggered by the combination of caffeine and exercise may be unfavorable without familiarity of the cardiovascular parameters and the individuals’ characteristics. These findings suggest that depending on physical activity intensity, caffeine may become a contributing factor for harmful cardiovascular complications following exercise in subjects with cardiovascular diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…As recognized above, caffeine supplementation in different populations is one of the ergogenic strategies investigated in the scientific research literature [3,7,11,15]. Considering that caffeine is consumed widely [16], detailed information regarding its impact on health is necessarily investigated, especially for its use in exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The association between performance and the consumption of energy drinks has been demonstrated in American football and soccer [12][13][14], athletics [15][16][17], volleyball [18], and handball [19], amongst others. Although there is comprehensive evidence of the positive association between the consumption of these drinks and improved sporting performance, there are risks in terms of the potential for cardiovascular problems due to hypertension, altered sleep patterns in adolescents, aggravation of mental illnesses, physiological dependence and an increased possibility of subsequent addiction [20,21], while their potential for toxicity can result in tachycardia, arrhythmia, vomiting, convulsions and even death [22]. The adverse effects of energy drink intake may occur in healthy people, but some people may be particularly prone to complications.…”
Section: Introductionmentioning
confidence: 99%